Control Schemes Comparative Study for Dual 6 DOF Arm Manipulators in Cooperative Task - Ahmed Kharidege; Mustfa Eler (African Journal of Advanced Pure and Applied Sciences, 2024)
This paper proposes the position control strategy for manipulating a dual-arm robot to improve the position accuracy for packing process. To complete a position motion of the dual manipulator’s end-effector, the position coordinates of each manipulator first required to be converted to a set of joint angles using the inverse kinematics method. The manipulators have six joints each, and each joint is driven by servomotor, and each joint rotation is executed using a motor feedback control. To demonstrate the performance of the controllers, first, PID Controller was designed. Then fuzzy logic controller was designed and system responses were investigated. The results show that the fuzzy controller provides improved performance with a smaller steady state error. The effectiveness of the proposed method was assured by experimental results of actual arm robots.